Peran Artificial Intelligence dalam Akuntansi: Analisis Bibliometrik - Indriani, Pravita (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The rapid development of Artificial Intelligence (AI) has significantly transformed various industries, including accounting. This study examines the integration of AI in accounting practices over the past seven years, focusing on recent research trends, dominant themes, and key contributors in the field. Using bibliometric analysis, 1,029 documents from Scopus were analyzed to uncover publication patterns, collaboration networks, and thematic clusters. Findings highlight the significant role of AI in enhancing operational efficiency through automated data entry, real-time anomaly detection, and predictive financial analysis. AI systems have also demonstrated the ability to reduce human error and enable accountants to focus on value-added strategic activities. However, challenges such as ethical concerns, data privacy issues, and the future of accounting professions persist. Thematic mapping reveals emerging applications like machine learning and deep learning, indicating foundational yet underdeveloped areas of study. This paper underscores the necessity for accounting education to adapt to technological advancements and provides insights into the strategic role of AI in modernizing accounting practices. The results aim to support professionals and researchers in navigating the opportunities and challenges presented by AI in accounting.